Performance Analysis of Concrete Slab Reinforced with Steel and Bamboo - Surenthiran, Iynkaran; Bogoda, Sakura (Advances in Technology, 2022)
Concrete and steel are considered the main construction materials in the world today while the cost of steel is rising year by year. Though steel can be recycled, it consumes a significant amount of energy in the manufacturing and recycling stages. Thus, to cope with that risk and reduce the building budget, it will be necessary to start using alternative resources. Studies were conducted to discover the appropriateness of using timber resources (e.g., Bamboo and Palmyra) to substitute steel as reinforcements in concrete. Bamboo is a quick-growing plant and is easily obtainable in the Asia region. Bamboo has a higher tensile strength than other timber resources and strength to weight proportion. However, due to its brittle behavior, bamboo cannot fully replace steel. Characteristics of bamboo differ with its time of life and class. The main aim of this research is to suggest a suitable hybrid reinforcement with steel and bamboo for the construction industry by analyzing the concrete slab element. This paper discusses the behavior of concrete slabs, reinforced with steel and bamboo and the applicability of Finite Element Modelling (FEM) using the ABAQUS software. The numerical model was validated by the experimental investigation in the literature.